2018
DOI: 10.1101/375618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AKT regulates mitotic progression of mammalian cells by phosphorylating MASTL

Abstract: Microtubule associated serine threonine like kinase (MASTL) has been recently identified as an important regulator of mitosis. By inhibiting protein phosphatase 2A, it plays a crucial role in activating one of the most important mitotic kinases known as cyclin dependent kinase1 (CDK1). MASTL has been seen to be up regulated in various types of cancers and is involved in tumor recurrence. It is activated by CDK1 through its auto regulatory loop but the complete mechanism of its activation is still unclear. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It is, therefore, possible that MASTL may influence AKT signaling differentially in cycling (Vera et al , 2015) or starved/G0 cells as suggested by our data. Interestingly, AKT may lead to MASTL phosphorylation and activation specifically during mitosis (Reshi et al , 2020), although whether this is mediated by direct phosphorylation and whether these data have any relevance in vivo in a physiological context have not been addressed so far.…”
Section: Discussionmentioning
confidence: 99%
“…It is, therefore, possible that MASTL may influence AKT signaling differentially in cycling (Vera et al , 2015) or starved/G0 cells as suggested by our data. Interestingly, AKT may lead to MASTL phosphorylation and activation specifically during mitosis (Reshi et al , 2020), although whether this is mediated by direct phosphorylation and whether these data have any relevance in vivo in a physiological context have not been addressed so far.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that MASTL may influence AKT signaling differentially in cycling 39 or starved/G0 cells as suggested by our data. Interestingly, AKT may lead to MASTL phosphorylation and activation specifically during mitosis 40 , although whether this is mediated by direct phosphorylation and whether these data have any relevance in vivo in a physiological context has not been addressed so far.…”
Section: Discussionmentioning
confidence: 99%